Lip Asymmetry and Smile Aesthetics. (November 2013) - Batwa, Waeil; McDonald, Fraser; Cash, Alex
Objective: To determine if lip asymmetry can affect lip aesthetics. Setting and Participants: A group of dentists (n = 40) and cleft patients (n = 40) were recruited from the dental hospital and cleft service. Interventions: Still photographic digital images of lips and teeth were manipulated to produce a computerized gradient of smile appearance with different degrees of upper-lip vertical asymmetry. These five photographs (with 0 mm representing "symmetry, " and 1, 2, 2.5, and 3 mm, asymmetries) were assessed by participants using a 5-point Likert scale. Statistics: Descriptive statistics in addition to chi-square test were used to analyze the data. In order to satisfy the requirement of the chi-square test, the five smile ratings were reduced to three. Results: Lip asymmetry did affect relative smile aesthetics, as determined by dentists and cleft patients. Both the dentists and cleft patients rated the 0-mm photograph more attractive than the 2.5-mm and 3-mm smiles ( P < .05). The 0-, 1-, and 2-mm smiles were indistinguishable for both dentists and cleft patients. Conclusion: Lip asymmetry affects smile aesthetics. However, cleft patients and dentists were tolerant of minor asymmetries. This suggests that small degrees of lip asymmetry do not affect relative smile aesthetics as much as large degrees of lip asymmetry (2.5 mm or more).